اناجیلِ اربعہ پر ابن حزم کی تنقید کے شواہدEvidences of Criticism on the Authenticity of four Gospels by Ibn-e-Hazm (Al-Qamar, 2022)
Ibn-e-Hazm is one of the prominent scholars of Islam who gained fame among Muslims and non-Muslims for his scholarly work about religious studies. Ibn-e-Hazm’s book “Kitab-ul-Fasl Fi al-Milal wa al-Ahail wa al-Nihal” is about comparative studies of religions. The book got popularity among Muslim and non-Muslim scholars and different critics are seen about his approach towards the understanding of world’s religions. The author of the article “The Encyclopedia of Islam” has claimed that Ibn-e-Hazm’s approach towards criticizing the historical authenticity of the Bible is not academic rather he wrote the chapter in his book with narrow-mindedness. This study deals with this allegation and the author has tried to find out the historical evidence presented by Christian scholars to prove that Ibn-e-Hazm’s way of putting forward his opinion is academically perfect and each of his arguments is built upon solid and irrefutable references.
Keywords: Ibn-e-Hazm; Kitab al-Fasl; Christianity; Bible; Gospels; History